Participatory management and organizational involvement of employees in Sub-Saharan Africa - (:unkn) unknown (My University, 2019)
This article aims to analyze the effects of participatory management on the organizational involvement of employees in Halliburton, in a context marked by an increased search for performance and in an increasingly competitive environment. To achieve this, we conducted a quantitative survey of 451 employees of Halliburton and Perenco firms in Central and West Africa, in order to request their assessment of the level of implementation of participatory management in the company. as well as their organizational involvement. The descriptive analysis of the data shows that the participative management is strongly implanted in the firms and that the level of organizational involvement of employees is interesting. The inferential analysis through the simple linear regression indicates that there is a positive and significant influence of the participative management on the organizational implication of the employees of the firms. These results are discussed in the perspective of Stashevsky and Elizur (2000), Charles-Pauvers and Schieb-Bienfait (2012), Stervinou (2014) and Mahieu (2017) whose conclusions go in the same direction as ours and suggest that maintaining participatory management and extending it to all employees would contribute to improving their organizational involvement.
Keywords: African Research